Application of Cutinase in Ester Synthesis Industry - Zhan Zhi Liu (Cutinase: Preparation and Application, 2021)
Short-chain esters are commonly used as fruit flavorings in the food industry. T. fusca cutinase was used for the synthesis of aliphatic esters, and the maximum yields of ethyl caproate were 99.2% at the optimal condition: 50 U/mL T. fusca cutinase, 40\(^°\)C, and 0.5% water content, representing the highest yield of ester synthesis. The esterification that catalyzed by cutinase displayed strong tolerance for water content (up to 8%) and acid concentration (up to 0.8 M), respectively. The yields of ester synthesis remained above 80% at substrate concentrations \(\) 0.8 M. Moreover, ester yields were achieved more than 98% and 95% for acids of C3-C8 and alcohols of C1-C6, respectively, indicating extensive chain length selectivity of the cutinase. T. fusca cutinase has the superior ability to catalyze the synthesis of short-chain esters, which provided the basis for the industrial production of short-chain esters.